GAA‐FGF14 Expansions and CACNA1A Variants: Phenotypic Overlap and Diagnostic Implications - Indelicato, Elisabetta; Fleszar, Zofia; Pellerin, David; Nachbauer, Wolfgang; Zuchner, Stephan; Traschütz, Andreas; Amprosi, Matthias; Schöls, Ludger; Haack, Tobias B.; Brais, Bernard; Boesch, Sylvia; Synofzik, Matthis (Movement disorders, 2025)
Background An intronic (GAA)•(TTC) repeat expansion in FGF14 was recently identified as the cause of spinocerebellar ataxia 27B (SCA27B), a disorder presenting with both chronic cerebellar ataxia and episodic symptoms. The phenotype of SCA27B overlaps with that of CACNA1A spectrum disorders. Objective The objective of this work was to investigate the prevalence of GAA‐FGF14 repeat expansions in patients with ataxia so far considered to be related to underlying CACNA1A variants. Methods This is a cross‐sectional multicenter study. Results GAA‐FGF14 testing showed pathogenic expansions (≥250 repeats) in 6/67 (9%) patients carrying CACNA1A variants. All patients with a pathogenic GAA‐FGF14 expansion had a disease onset >40 years and carried variants of uncertain significance (VUSs) in CACNA1A. Genetic reevaluation led to the reclassification of CACNA1A VUSs as likely benign in four of six patients, who were ultimately diagnosed with SCA27B. Conclusions Late‐onset ataxia cases previously considered as CACNA1A‐related disorder should be reevaluated and tested for SCA27B, particularly if related to a VUS in CACNA1A. © 2025 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.